Overcoming poor ovarian reserve: a case report series of spontaneous conception after failed intracytoplasmic sperm injection - Mariyappan, Scindiya; Anand, Papitha P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
This case report addresses the possibility of spontaneous conception in women with diminished poor ovarian reserve (POR) after multiple failure of assisted reproductive technology (ART) cycles, including intrauterine insemination (IUI) and intracytoplasmic sperm injection (ICSI). Four cases were analyzed, including patients aged 31 to 41 years, each with a unique clinical profile for POR. These patients were infertile for durations of 5 to 12 years, as well as with other conditions like hypothyroidism and raised BMI. Recombinant FSH was used in all cases for ovarian stimulation, but the outcome was suboptimal with poor oocyte retrieval rates and fertilization failure. The cumulative follicle-stimulating hormone (FSH) dose used in patients ranged from 1875 IU to 3000 IU. This strategy produced a low yield of oocytes, most of which were immature or failed to fertilize. Remarkably, all four patients subsequently conceived spontaneously and gave birth to healthy babies without additional ART treatments, despite the difficulty encountered in the ART cycles. The observation that spontaneous conception was successful in these complicated cases underscores the need for further studies into the mechanisms underlying such events to occur, especially in patients who have had multiple failure with ART. This case report underscores the merit of individualized treatment strategies and continued investigation into the determinants influencing fertility in women with POR.